Establishing Autonomy and Responsibilities of Science Writers - Ana Nadhya Abrar; I Gusti Ngurah Putra; Adam Wijoyo Sukarno; Desmalinda Desmalinda; Mirfath Mirfath (Ikatan Sarjana Komunikasi Indonesia, 2023)
An important theme of science communication research is research on science article writers. However, not many scholars are interested in doing this research. Based on this fact, we conducted a research on the ideal position of a science article writer. It turns out that he definition of science writer has changed in Indonesia. Quantitative content analysis of articles reported by The Conversation Indonesia during December 2021 found that the writerss motivated the public to understand and use scientific principles to meet their daily needs. The results of in-depth interviews with three prominent professors at Universitas Gadjah Mada confirm the same fact. They do not just tell the object of research in a certain context. This fact certainly needs to be imitated by other science writers. However, there is a basic recipe that must be practiced by other science writers. The practice of the recipe will make them autonomous and responsible to society. Thus, the article will explain the ways that can be taken to make it happen.